The Wage Premium to a University Education in Canada, 1971-1991 - Bar-Or, Yuval; Burbidge, John; Magee, Lonnie; Robb, A. Leslie (Journal of Labor Economics, 1995)
Using micro data from the Canadian Survey of Consumer Finances, 1971-91, we investigate the return to a university education. Our conclusions are that while there appears to have been some decline in the return to a university degree during the 1970s in Canada (similar to the United States), the return did not rebound much during the 1980s except among the youngest experience (age) group. There is, however, considerable noise in the ratios from year to year so that one is likely to draw misleading inferences if only a few years of data are used.